Evaluation of human platelet lysate as an alternative growth factor for expansion and hepatocyte differentiation of dental pulp stem cells / Aimi Naim Abdullah - Aimi Naim, Abdullah (2012)
The advancement of stem cells research has pushed the fronteir of regenerative medicine to a different level where range of diseases including liver diseases could be potentially treated using cell therapy. The usage of stem cells offers alternative treatment to organ transplantation, wherein, organ shortage issue and possibility of rejection are major limitations. Dental pulp stem cells from deciduous teeth (SCD) have been identified as a source of adult stem cells with high proliferation activity and multilineage differentiation. Current studies showed that SCD have potential to differentiate into hepatic lineage and they usually cultured in fetal bovine serum (FBS) supplemented media. Thus, this may expose SCD to the possibility of contamination to virus, prions, mycoplasma and transmission of disease. It is necessary to identify animal-free serum media if cell therapy is to play a major role in regenerative medicine. Human platelet lysate (HPL) appears to be a suitable substitution to FBS for stem cells culture as it is a non-animal origin and has a lot of natural growth factors to support stem cells proliferation and differentiation. The aim of this study was firstly to evaluate HPL as an alternative culture media to FBS in the culture, expansion and differentiation of SCD. Secondly, the ability of SCD to differentiate into hepatocyte differentiation when cultured in FBS and HPL will also be assesed. The properties of SCD cultured in both media were examined through growth kinetics, trilineages differentiation and expression of specific surface markers. The differentiation potential of SCD in FBS and HPL into hepatocyte-like cells was investigated from the morphological formation, periodic acid Schiff (PAS) staining and the expression of hepatocyte specific marker with urea secretion assay at day 0, 7, 14 and 21. Results showed SCD cultured in HPL has higher proliferation rate compared to FBS and displayed similar potential of trilineage differentiation and phenotypic expressions. SCD cultured in both media also displayed potential to form hepatocyte-like cells based on the morphology changes from fibroblast to hexagonal-shaped cells and positive staining for PAS. The expression of hepatocyte specific markers and the urea secretion increased proportionally with the day of hepatocyte induction. Within the limitations in this study, it could be conclude that HPL could be an alternative to FBS as the proliferation of SCD cultured in HPL is statistically higher and exhibited similar characteristic to FBS. SCD in HPL also showed potential to differentiate into hepatocyte cells and thus may become a hope for alternative treatment of liver diseases.